Reflexion of citizens´ needs in city strategies: The case study of selected cities of Visegrad group countries - Kopáčková, Hana (My University, 2019)
Citizen-centric approach calls for respecting citizens' needs in strategic planning without defining them. This article reveals the gap in the definition of citizens´ needs concept, and as a response, it proposes comprehensive specification. Special attention is given to satisfaction surveys and the explanation of the relationship between citizens' needs and strategic planning. The case study explores two Flash Eurobarometer reports on Quality of Life in European Cities and strategic plans of selected cities to find out if the needs of citizens are respected. As the examples, for the case study, are selected cities of Visegrad group countries for their common totalitarian history and cultural proximity. Satisfaction surveys are utilized in both ways; as the product of strategic planning and as the input to strategic planning. The product view brings the answer to the question how successful cities are in dealing with problem issues. The input view takes current problem issues and compares them with future strategic plans to see if they include solutions to problem issues.
Reflexe potřeb občanů v městských strategiích: případová studie vybraných měst zemí visegrádské skupiny
Keywords: Citizen-centric approach; Citizens´needs; Visegrad group; European Union; Satisfaction; Maslow; přístup zaměřený na občany; potřeby občanů; Visegradská skupina; Evropská unie; spokojenost; Maslow